2017
DOI: 10.1212/wnl.0000000000003630
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic lesions, blood pressure dysregulation, and poor outcomes in intracerebral hemorrhage

Abstract: Objective: To evaluate the associations among diffusion-weighted imaging (DWI) lesions, blood pressure (BP) dysregulation, MRI markers of small vessel disease, and poor outcome in a large, prospective study of primary intracerebral hemorrhage (ICH). Methods:The Ethnic/Racial Variations of Intracerebral Hemorrhage (ERICH) study is a multicenter, observational study of ICH among white, black, and Hispanic patients.Results: Of 600 patients, mean (6SD) age was 60.8 6 13.6 years, median (interquartile range) ICH vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
121
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(130 citation statements)
references
References 32 publications
5
121
4
Order By: Relevance
“…In our cohort, we observed acute ischaemic lesions among 15.5% of patients with acute ICH within 10 days after symptom onset. These results are in line with the prevalence reported in previous studies, ranging from 11% to 41% . As previously described, we found that patients with lobar ICH more frequently had DWI lesions than those with deep ICH .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our cohort, we observed acute ischaemic lesions among 15.5% of patients with acute ICH within 10 days after symptom onset. These results are in line with the prevalence reported in previous studies, ranging from 11% to 41% . As previously described, we found that patients with lobar ICH more frequently had DWI lesions than those with deep ICH .…”
Section: Discussionsupporting
confidence: 93%
“…The mechanisms and etiology of DWI lesions in patients with acute ICH remain uncertain. Previous studies have linked DWI lesions to underlying SVD . DWI lesions are more frequently observed in CAA‐ICH and are associated with markers of CAA including lobar CMB, WMHs and enlarged perivascular spaces in the centrum semiovale .…”
Section: Discussionmentioning
confidence: 99%
“…A recent population‐based autopsy study also showed an association between premortem BP decline over time and the occurrence of microinfarcts . Similarly, the occurrence of CMI after hemorrhagic stroke has been associated with more aggressive reduction in BP after admission . Furthermore, in a hemorrhagic stroke model in mice, both amyloid deposition and microinfarct count increased after chronic hypoperfusion due to bilateral carotid artery stenosis .…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, the presence of intracerebral remote diffusion‐weighted imaging lesions (R‐DWILs) has been known to worsen the stroke outcome . R‐DWILs are defined as focal hyperintensities remote from the site of the ICH or the peri‐hematoma region on diffusion‐weighted images, which are detected in about 11%‐41% of ICH patients . It is an essential complication that requires attention owing to its significant effect on the increased risk of recurrent ICH, cognitive impairment, and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the progression of microangiopathy, inflammatory response following ICH has also been implicated to exert influence on the development of R‐DWILs . However, prior studies examining the effect of inflammation, in the form of leukocytes, had failed to find a correlation with R‐DWILs . It was possible that they analyzed leukocytes as an entirety instead of a subset and neglected the respective implications of neutrophils or lymphocytes following ICH.…”
Section: Introductionmentioning
confidence: 99%